Selective Removal of 2,4-Dichlorophenol by Surface Molecularly Imprinted Polymers Based on Amino-Functionalized FeO@SiO Composites - Jinyu Chu; Bing Wang; Yujun Song; Xiaohua Zou; Chunxiang Li; Yongsheng Yan (Adsorption Science & Technology)
A highly selective imprinted amino-functionalized Fe 3 O 4 @SiO 2 sorbent was prepared by surface molecular imprinting technique for selective removal of trace 2,4-dichlorophenol (2,4-DCP) in water samples. The 2,4-DCP-imprinted amino-functionalized Fe 3 O 4 @SiO 2 sorbent was characterized by Fourier transform infrared, transmission electron microscopy, vibrating sample magnetometer, thermogravimetric analysis and batch-mode binding studies. The imprinted functionalized Fe 3 O 4 @SiO 2 sorbent exhibited high selectivity and offered a fast kinetics for the adsorption of 2,4-DCP. The prepared sorbent was shown to be promising for selective removal of trace levels of 2,4-DCP in environmental water samples.